The 2019/20 Australian wildfires generated a persistent smoke-charged vortex rising up to 35 km altitude - Sergey Khaykin (Nature Portfolio, 2020)
The 2019/2020 Australian wildfires generated a smoke cloud that organized itself into a persistent vortex structure and ascended to 35 km altitude through solar heating, according to satellite tracking.